Photocatalytic degradation of low-density polythene using protein-coated titania nanoparticles and Lactobacillus plantarum. Issue 5 (23rd February 2023) - Dave, Divyeshkumar; Chauhan, Kamlesh; Khimani, Ankurkumar; Soni, Krina; Vaidya, Yati
ABSTRACT: The biodegradation of low-density Polyethylene (LDPE) is usually time-consuming, In the presence of Titania-nanoparticles, LDPE is photocatalytically degraded in smaller fragments afterward the bacteria can effectively degrade polyethylene. In the current study, potent polyethylene degrading bacteria were screened from the soil of the local dumpsite and identified using 16s rRNA sequencing. The protein-coated titania nanoparticle (TNPs) was synthesized using Sol-gel Method and characterized by XRD, and SAED-HRTEM. The photocatalytic biodegradation of LDPE (30 microns) in presence of 1M NaOH was studied by exposing it to UV irradiation, visible light, and high temperature (50°C) for 21 days separately and photocatalytic biodegradation was assessed by monitoring % weight loss at every 7 days' time interval, tensile strength, and FTIR. After 21 days of photocatalytic biodegradation, LDPE film containing both TNPs and Lactobacillus plantarum along with 1M NaOH in presence of visible light was unveiled oxidation and enumerated via the occurrence of strong absorptions band of the carbonyl group (C=O) and also the breaking and weakening of existing absorptions bonds along with the new carbonyl functional group formation. The decline in tensile strength was measured at 21% after 21 days. Thus, experimental results on LDPE after exposure to visible irradiation along with Lactobacillus plantarum and 5% protein-coated TNP showed improvement in degradation rate and elongation 59 % and 51% within 21 days, respectively in comparison to another study (49 % Weight loss and 12% elongation after 45 days). An excellent application of this research is significantly reduced plastic waste via a maintained procedure. GRAPHICAL ABSTRACT: UF0001